Original paperTreatment of primary cutaneous lymphoma with reference to the latest therapeutic consensus of the Polish Lymphoma Research Group (PLRG) - Wojewoda, Karolina; Brenner, Jonas; Sokołowska-Wojdyło, Małgorzata; Barańska-Rybak, Wioletta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction : Primary cutaneous lymphomas are a heterogeneous collection of lymphoproliferative malignancies with a wide-ranging clinical picture, course and prognosis. Mycosis fungoides (MF) is the most common disease in this group. Mycosis fungoides, Sézary syndrome (SS) and lymphomatoid papulosis (LyP) are the most frequent primary cutaneous lymphomas treated in our department. Each disease requires a specific treatment, further adding complexity in this diverse group of pathologies. Aim : To evaluate methods and results of treatment used in patients with primary cutaneous T-cell lymphoma (CTCL), treated in the Department of Dermatology, Venereology and Allergology, Medical University of Gdansk in 2007-2011, with reference to SLS (Skin Lymphoma Section) of PLRG (Polish Lymphoma Research Group). Material and methods : One hundred sixty-three medical records of 68 hospitalized patients, with a suspected diagnosis of CTCL, were analyzed. The male-to-female ratio was 1 : 0.7, with the age range of 30-95 years. Results : Twenty-four patients with MF were treated with topical corticosteroids, 21 with phototherapy, 6 with retinoid (acitretin), 2 with bexarotene (alone or in the combination with PUVA/UVB311). Methotrexate in low doses was used in 19 patients and interferon α in 4 patients. Radiotherapy was used in 7 cases and chemotherapy (2CdA or CHOP) was used in 11 cases. Conclusions : It is difficult to evaluate the results of the treated group because of the short observation period. Not all methods of treatment suggested in the recommendations by the SChS PLRG and EORTC WHO were included.